Biotechnology as a tool for the agroindustrial exploitation of residues of the chain of musa spp. (2018)
Currently, one of the major problems of agricultural and agroindustry production chains worldwide, is generated by the by-products that later become contaminating sources of the environment. It is then, where the use of biotechnology as a tool applied to agroindustry processes manages to transform by-products into products with greater added value. For its part, the cultivation Musa spp., has been a traditional sector of the peasant economy, but at the same time it generates a significant amount of waste (pseudostem and leaves) that remain in the field after harvest. Therefore, it is proposed in this research to identify the potential of the pseudostem of Musa spp., as raw material for the development of nutritional blocks that serve for animal consumption, taking as a reference the characterization, pretreatment and combination of said byproduct with waste from other agroindustry chains, for their nutritional potential such as molasses, glycerin and the cake of palm kernel. In addition, two factors were evaluated: the first with pseudostem from of (San Francisco - Cundinamarca and Tibaná - Boyacá) and the second pre-treatment from (stem in cool and stem in silage); with these were constructed nutritional blocks considering the two research factors and their combinations to establish the behavior and nutritional quality of pretreatments. The results showed a reduction of the lignin level, an increase of the protein content up to 30%, as well as a decrease in the percentage of Neutral Detergent Fiber - NDF, converting of pseudostem blocks into a food supplement with great potential of use in the animal feed and with this in an alternative to mitigate the negative impact of the disposal of these residues in the environment. Copyright © 2018, AIDIC Servizi S.r.l.